NEW MODEL AND GENRE CONVENTIONS: A DEEP ANALYSIS OF THE INNOVATIONS IN CRAZY STONE - Wang Qi; Meng Ning (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This paper analyzes how Ning Hao’s Crazy Stone (2006) inherits and innovates the genre conventions of Chinese black comedy films. Since the 1980s, Chinese black comedy films have absorbed Western creative techniques and developed a unique genre style. Crazy Stone successfully breaks the traditional framework of black comedy by blending genres, employing multiple narrative lines, and incorporating localized expressions. The film combines absurd humor, social criticism, and cultural symbols, creating a new genre model that has had a profound impact on subsequent films of the same genre. However, as this model has been widely imitated, genre innovation now faces the challenge of aesthetic fatigue. Film creation must continuously break through conventions and drive the innovation of genre development.